Physical education curriculum model: Can FEM and SEM create participation in physical activity and enjoyment? - Amalia, Eneng Fitri; Setiawan, Edi; Kastrena, Ervan; Jumareng, Hasanuddin; Rahadian, Adi; Patah, Ihsan Abdul; Gani, Ruslan Abdul (UIR Press, 2021)
The low participation in physical activity and enjoyment among students is the main problem factor in this study. The purpose of this study is to try to increase participation in physical activity and student enjoyment through FEM and SEM which are integrated into physical education learning. This study is using quantitative research with experimental methods. 30 students Departement of Physical Education, Health, and Reacreation from Universitas Suryakancana are willing to be the subjects in this research. The research instrument uses IPAQ and EPESC. Data analysis uses IBM SPSS version 25 with a significance level of 0.05. The results of this study find that both of FEM and SEM have a significant impact on increasing students’ participation in physical activity and enjoyment. This study confirms that FEM and SEM are pedagogical tools that lecturers can use to change participation in students’ physical activity and enjoyment from low to high.